Improved Exponential Approach Method in Determining Optimum Solutions for Transportation Problems - Rusli, Rusli; Sukarna, Sukarna; Wahyudin, Wahyudin (ARRUS Journal of Mathematics and Applied Science, 2022)
This study describes the transportation methods that regulate and distribute resources that provide products where they are needed to achieve efficient transportation costs. Solve a transportation problem in this thesis using the Improved Exponential Approach method, then using the NWC (Northwest) method to test its optimization. The purpose of this research is to get more optimal results as initial consideration to increase the distribution cost savings in the Bread Company. Costs incurred by the company before the study amounted to Rp.3,218,000. The results of this study found that the application of the transportation method using the Improved Exponential Approach method is effectively used compared to the NWC method which has a comparison of transportation costs of Rp. 2,612,500 and Rp. 2,785,000, Optimization test results obtained from the Improved Exponential Approach method amounted to Rp2,612,500. And the Improved Exponential Approach method used by researchers can be applied to the Gardenia company.